KH. Ahmad Dahlan and the Muhammadiyah Movement: Trailblazers of Educational Transformation in Indonesia - Maraulang, Maraulang (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
KH. Ahmad Dahlan, born Muhammad Darwis in 1868 in Yogyakarta, was a scholar, educator, and reformer who founded Muhammadiyah in 1912. He was concerned with education and religious understanding among Indonesian Muslims, who were lagging. Muhammadiyah aimed to advance education, health, and social welfare by establishing schools that integrated religious and secular knowledge. Before Muhammadiyah, education in Indonesia was dominated by traditional pesantren and madrasah, with less relevant methods to contemporary developments. KH. Ahmad Dahlan introduced modern teaching methods that encouraged critical thinking and understanding. This study employs a literature review method to explore the contributions of KH. Ahmad Dahlan and the Muhammadiyah movement are transforming education in Indonesia. Data were collected from academic journals, books, conference papers, and credible online sources discussing the history, philosophy, and influence of KH. Ahmad Dahlan and Muhammadiyah. The research findings indicate that KH. Ahmad Dahlan and Muhammadiyah brought significant changes to Indonesian education by integrating religious and secular education, using the Indonesian language as the medium of instruction, emphasizing character education, and promoting gender equality. Muhammadiyah also introduced modern teaching methods and holistic social services. These contributions have enhanced access to and quality education, strengthened national identity, and influenced national education policies. This study provides a deep understanding of the pivotal role of KH. Ahmad Dahlan and Muhammadiyah, in educational reform, offer valuable lessons for the future development of the education system.